(untitled) (Advances in Military Technology, 2018)
The article deals with the statistics of aviation accidents associated with the ejection of the crew in military jet fighter, fighter-trainer and trainer aircraft in the service of Czechoslovakia and the Czech Republic from 1948 until the end of 2016. It presents a unique, previously unpublished comprehensive overview of aviation accidents (disasters, air crashes and damage) in which the crew ejected, as well as a critical analysis of types of events involved, date of their origin, type and version of the aircraft and also the number of killed and rescued crew members. The figures are accompanied by numerous annotations and an overview of still accessible reference and information sources on the subject.